Cloud-based accounting intelligence application: opportunities and challenges to information system / Fa'izah Ghazi and Norizam Ahmad @ Muhammad - Fa'izah Ghazi, Fa'izah; Ahmad@ Muhammad, Norizam (Fakulti Perakaunan, 2023)
The accounting profession has experienced difficulties due to the growing complexity of corporate environments, as well as increased global competition and a flattening out of business cycles. The digitization of business, the serious potential of the Web, the implications of big data, and the growing significance of infornation mining have impacted businesses, including the accounting offices (Moudud-UI-Huq et al., 2020).